MACKEREL TUNA (EUTHYNNUS AFFINIS) SUPPLY CHAIN AT THE BELAWAN OCEAN FISHING PORT, NORTH SUMATERA PROVINCE - Hasan Sitorus; Kimberly Febrina Kodrat (CV. Radja Publika, 2024)
This research aims to determine the supply chain for tuna fish at the Belawan Ocean Fisheries Port (PPS). The research was conducted at the Belawan Ocean Fisheries Port (PPS), North Sumatera Province. The data collected included observation, interviews and literature research (excavating secondary sources). The research results show that the results of the analysis of the tuna fish supply chain show that there are four supply chains and four actors. The shorter the supply chain and the smaller the marketing margin, the greater the profits and marketing costs received. This indicates that marketing of tuna fishery production will be more efficient, and vice versa. The shortest supply chain alternative is highly recommended to ensure stock availability, minimize prices, increase profits, empower local assets and culture of North Sumatara Province which must be maintained, and the role and contribution of the government is really needed, especially when the availability of tuna stocks is abundant.